“Extrarregional” Migration and Temporary Borders in the Recent South American Context. Haitian Migration and “Legal Intermittency” in Argentina - Trabalón, Carina (2023)
This article aims to analyze the tensions and reconfigurations that operate between illegalization, temporary borders and daily life of Haitians in Argentina, in connection with larger regional processes linked to the political government of Caribbean and African “extrarregional” migration in the recent South American context. I argue that the control over the modes of “permanence” of migrants of Haitian origin in Argentina represents a paradigmatic case that allows exposing regional trends in progress during the 2010s, based on the political exclusion of the refuge, the existence of differential criteria of residence, the reinforcement of illegalization mechanisms and the multiplication of temporary borders. In addition, I maintain that one of the main manifestations of these political processes is the “legal intermittency” referring to the conflictive and changing dynamics that is established between legal-political practices, temporary experiences of control and negotiation strategies of the subjects. The article adopts a qualitative methodological approach that includes, firstly, a documentary analysis of regulations and policies implemented at the regional level during the 2010s on Caribbean and African migration in Argentina, Brazil, Chile and Ecuador. Second, a participant observation and interviews conducted with migrants of Haitian origin between 2017 and 2019 in two cities in Argentina. I conclude that the link between legal borders and temporary borders constitutes a key aspect to understand both the political-administrative realities of the “new” migrations in the South American context, as well as the historically situated ways in which “configurations of illegality” permeate the projects of life and forms of resistance of specific national and social groups.